СЕЙФУЛҒАБИТ МАЖИТОВТЫҢ ЖӘДИДШИЛИК-АҒАРТЫЎШЫЛЫҚ ХЫЗМЕТЛЕРИ - Сейтмуратов, Қ. (SCIENCE and SOCIETY, 2025)
The article talks about the educational – jadid activities and pedagogical views of Seyfulgabid Majidov, a famous poet-educator.
Keywords: jadidism; Jadid schools; education; independence; poetry; alphabet; drama; textbook